Women's wellbeing in Local Government Councils of Sri Lanka: Political engagement and new gains under quota-mandated female representation - Chandran, S. (University of Colombo, Sri Lanka., 2019)
Local government is an important avenue for obtaining practical experience in participating in politics, before moving on to the national arena. Advocates of quota-mandated representation argue that it opens up avenues for women to articulate their interests, enter arenas of political decision-making, and advance women's interests.
Keywords: local government, political representation, quota system, wellbeing